DEVELOPMENT OF A WEB-BASED RAW MATERIAL INVENTORY INFORMATION SYSTEM TO ENHANCE OPERATIONAL EFFICIENCY IN MSMES: A CASE STUDY OF DRINK MR. BONES - Rahman, Saepul; Sandi, Aries; Septiani, Anny; Adi Sunarto, Asril (Buana Informatika, 2025)
UMKM Drink MR. Bones is a micro-business in the culinary field located in Cisaat, Sukabumi. Currently, raw material inventory management is carried out manually with simple recording in books, so it is prone to errors, inefficient, and time-consuming in reporting. To overcome this, a Web-Based Raw Material Inventory Information System was designed that can help the process of recording, monitoring, and reporting stock digitally and in real-time. The system was developed using PHP as the backend and MySQL as the database, with an object-oriented design approach using UML. The development methodology refers to the Waterfall model in the System Development Life Cycle (SDLC), including needs analysis, system design, implementation, testing, deployment, and maintenance. The results of the study show that this information system is able to increase the effectiveness and efficiency of raw material management, reduce recording errors, accelerate reporting, and support smooth production according to market demand.